Financial/economic incentives to support water savings and water productivity improvements in Uzbekistan [Abstract only] - Anarbekov, Oyture; Solieva, G. N. U. (2018)
Agriculture is an essential sector of Uzbekistan’s economy, with 17.6% of GDP in 2016 and engaging about 26% of the labor force. Having dry climatic conditions, with annual rainfall of 100–300 mm, agriculture is an abundant consumer of the country’s natural resources. More precisely, the agricultural sector constitutes 92% of Uzbekistan’s total water use, which is on average of 56 billion cubic meters of water. This is equal to 60% of all water use in Central Asia. By 2020, irrigated area of Uzbekistan is forecast to increase between 5 and 11% and overall demand for water resources could increase up to 19%. Taking into account the growing pressure on water resources, the Government of Uzbekistan is introducing water conservation policies to mitigate existing and future stresses to water sector. However, to date neither incentives to introduce water saving technologies nor penalties on water users for violating the order of water use have been effective. A lack of incentives for water savings is a key factor affecting water use decisions. In Uzbekistan, water supply for water users (municipal services, agriculture, industry, energy, etc.) is at the expense of the state budget and considered free of charge for the users. Thus, government interventions aimed at the rational use of water resources have minimal impact. This could explain the fact that water application by farmers often exceeds, by several times, the biological requirement for agricultural crops. The objective of this study is to investigate financial/economic incentives to support water savings and water productivity improvements at on-farm level in Uzbekistan. To undertake this research the two-part tariff methodology is being applied as an experiment in three selected Water Consumer Associations in three Provinces of Uzbekistan, representing varied natural and climatic regions. Mini-gauging stations were installed and used as so call Smartsticks (low-cost, crowd-sensed technology) to measure discharge. The approach estimates the constant and variable expenses of Water Consumer Associations (WCA) when the water fee is simultaneously linked with crop area and water volume. The results will show the effects of water pricing (i.e. Irrigation service fee) and whether payment for irrigation water can influence the water consumption behavior of farmers. The study outcomes can form the base to recommend new water payment policies at the WCAs level, which in turn can have widespread influence on rational water use and collected revenue for water delivering organizations across regions.